Rīgas arhitektūras mantojuma aizsardzības jautājumi Latvijas preses izdevumos starpkaru posmā - Obodova, Sandra (Latvijas Universitāte, 2017)
Rīgas arhitektūras daudzveidība un izteiksmīgums ir tas, kas piesaista uzmanību Vecrīgai. Vecrīga kā pilsētbūvnieciskais ansamblis ir augstu novērtēta. Rīgas pilsēta pirmajos pēckara gados sāka formēties kā pilsētas pašvaldība, kurai bija jārisina daudzas problēmas. Rīgas pilsētai bija visvairāk aizsargājamo pieminekļu, par kuriem vajadzēja rūpēties. Šajā laika posmā Rīgas pašvaldība pievērsās Rīgas ģenerālplāna izstrādei, lai izveidotu Rīgas robežu plānu. Maģistra darba mērķis ir izpētīt Rīgas arhitektūras pieminekļu aizsardzības jautājumus starpkaru perioda presē, aplūkojot to kā vēsturisko procesu, ko ietekmē laikmeta sociālpolitisko un kultūrvēsturisko faktoru mijiedarbība. Maģistra darbā aplūkotais laika periods aptver laika posmu no 1920. gada līdz 1940. gadam. Darbā tiek aplūkota valsts institucionālā darbība un organizāciju ietekme Rīgas arhitektūras pieminekļu aizsardzības jautājumos. Aplūkota arī Rīgas pašvaldības darbība no 1920. gada līdz 1934. gadam un Rīgas pašvaldības darbība no 1934. gada līdz 1940. gadam, un tiek aplūkots, kā veidojās Rīgas pašvaldība un kā Rīgas pašvaldībā notika arhitektonisko pieminekļu aizsardzība. Rīgas arhitektūras aizsardzības mantojuma jautājuma atspoguļojums presē. Vispārējs Rīgas arhitektūras stilu raksturojums XX gadsimta 20.–40.gados un Rīgas arhitektūras aizsardzības mantojuma jautājuma atspoguļojums; kā presē tiek atspoguļots Rīgas arhitektūras laikmetu mantojums, ko veido daudzas kultūras pieminekļu sarakstā iekļautās ēkas un celtņu kompleksi.

The variety and expressive nature of Riga architecture is what attracts attention to the Old Riga. Old Riga has been highly evaluated for its town-planning ensemble. During the first post-war years, the Riga City started to shape itself into a city municipality that had many problems to solve. The Riga City had the most protected monuments that had to be taken care of. During this time the Riga municipality started designing the general plan of Riga in order to work out the plan of Riga borders. The objective of this Master thesis is to research the issues of protection of Riga architectural monuments in the press during the interwar period, investigating it as a historical process influenced by the interaction of socially political and culturally historical factors. The scope of this Master thesis includes the period from 1920 till 1940. The thesis looks at the institutional activities of the state and hot the state institutions and organizations influence the issues of protecting Riga architectural monuments. The thesis touches upon the operation of Riga City Council from 1920 till 1940. It also looks at the interwar period press regarding the opinions expressed therein about the architectural monuments of Riga. The Master thesis features research on the national and municipal aspect of protection of architectural heritage. It looks upon the origins of the Board of Monuments and the bill on protection of monuments which prescribed the creation of a list of architectural monuments that should be protected. At first the list included all objects in Old Riga. The thesis also looks upon the operation of Riga City Municipality from 1920 till 1934, investigates how the Riga municipality was formed and how the architectural monuments are protected in Riga municipality. A reflection of the issue of protecting Riga architectural heritage in the press. A general characterization of Riga architectural styles during the 1920-40ies and a reflection of the issue of protecting Riga architectural heritage in the press, namely, how the press reflects the heritage of Riga architectural eras that encompass many buildings and building complexes included in the list of cultural monuments.
Riga architectural heritage protection issues in Latvian press in the interwar period
Keywords: Vēsture; Rīgas arhitektūras aizsardzība; Rīgas arhitektūra; aizsardzība; prese; starpkaru